Spectral amplification of seismic oscillations by soils on the territory of Kyiv - Kendzera, O.V.; Semenova, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The article presents the results of modeling the reaction of soil of the territory of Kiev to the seismic load during an earthquake. The analysis of the soil response to the seismic loading aims to determine the effect of local soil conditions on the amplification of seismic vibrations and, therefore, to assess the soil response spectra for future seismic design purposes. Within the territory of Kiev, relatively homogeneous engineering-geological areas (taxonometric zones) have been identified, where the seismic effect can differ significantly. For each taxonometric zone, the integral coefficients of spectral amplification of seismic oscillations are calculated due to the influence of local soil conditions. The paper presents a map of the distribution of the deviation of the integral gain of seismic vibrations by soils from the average value for the territory of Kyiv. The constructed map of the distribution of the deviation of the integral gain of seismic vibrations from the mean value by soils is proposed to be used for making corrections, when applying the spectral method of calculation for an emergency combination of loads, taking the seismic effect into account to determine the value of the calculated relative peak ground acceleration of the construction site under study.